Right ventricular non-compaction: myth or reality?. (8th February 2021) - Kiss, A; Gregor, ZS; Horvath, M; Furak, A; Szabo, LE; Toth, A; Dohy, ZS; Czimbalmos, CS; Vago, H; Merkely, B; Szucs, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Noncompaction cardiomyopathy (NCMP) is characterized by excessive left ventricular (LV) trabeculation. The involvement of the right ventricle (RV) is still questionable, furthermore, the normal range for RV trabeculation is undefined.  Our aim was to describe the RV functional and strain values of patients with NCMP with preserved LV ejection fraction (EF) using cardiac MRI and to compare these parameters with healthy control subjects, furthermore, we aimed to define the normal range for RV trabeculation.  We included 81 NCMP patients with good LV-EF (mean age: 37.0 ± 14 years; EF: 69.4 ± 13.2%) and without comorbidities. Their parameters were compared to an age and sex matched control group (mean age: 37.2 ± 13.7 years; EF: 77.2 ± 15.0%). MR examinations were performed with 1, 5T Philips Achieva and Siemens Aera devices. The Medis Suite software was used for post-processing analysis, the MedCalc software for statistics, p < 0.05 was considered statistically significant.  The RV trabecular mass index (RV-TRABi) was significantly greater and the RV-EF significantly smaller in the NCMP group compared with the controls (NCMP vs. control; TRABi: 20.6 ± 7.0 vs. 16.9 ± 4.2 g/m2; RV-EF: 62.8 ± 5.5 vs. 64.5 ± 4.5%; p < 0.05). As for the RV global longitudinal strain (GLS) the results were close to significant (NCMP vs. control: -25.1 ± 4.0 vs. -26.4 ± 4.3%; p = 0.05). We defined the normal range of RV-TRABi with a lower limit of 8.2 g/m2 (90% confidence interval (CI): 6.8-9.5) and the upper limit of 22.1 g/m2 (90% CI: 23.6-26.5). 27.2% of the NCMP patients exceeded the upper limit of RV-TRABi.  The described differences in the RV-EF, RV-TRABi and RV-GLS draws attention to the possibility of the involvement of RV in patients with NCMP. Further follow-up studies would be necessary to evaluate the clinical importance of these alterations.